Clinical Implementation of Bone Regeneration and Maintenance - Barbeck, Mike; Rosenberg, Nahum; Rider, Patrick; Perić Kačarević, Željka; Jung, Ole (IntechOpen, 2021)
Bone healing and regeneration is a complex process that can become impaired by disease or the size of a bone fracture or defect. In these instances, bone grafting can be used to aid the regeneration process. Bone grafting materials can be divided into autologous, allogenic, xenogeneic, and alloplastic, and are used to fill the defect/fracture void, thereby providing stability and supporting the infiltration of surrounding bone. This book will cover the most important fundamentals of bone grafting and provide an overview of current and future trends in bone graft research. Over the course of this book, the reader will learn about the most recent advancements in bone tissue biomaterials, the different fabrication techniques of bone tissue scaffolds, and the interaction of bone graft implant materials with the body by their induced cell and tissue reactions. Overall, this book provides an insight into bone grafting and the requirements for successful bone regeneration.